Pulmonary embolism diagnosis : a clinical comparison between conventional planar and SPECT V/Q imaging using Krypton 81m – with CTPA as the gold standard - Ngoya, Patrick Sitati (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScMedSC (Medical Imaging and Clinical Oncology. Nuclear Medicine))--University of Stellenbosch, 2010.